The effectiveness of the Articulate Storyline Media Assisted Probing-Prompting Approach on Science Concept Comprehension in Elementary Schools - Hardiansyah, Framz (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the effectiveness of the application of the probing prompting model assisted by articulate storyline media in improving elementary school students' understanding of natural science concepts. The research design used a quasi-experimental nonequivalent control group design with a control group and an experimental group. The research subjects were 70 elementary school students, where 35 students were in the experimental group and 35 students were in the control group. Data collection was done using multiple-choice tests. Data analysis was carried out using the Kolmogorov-Smirnov normality test, the Levene homogeneity test, the independent sample t-test, and the N-gain test. The results showed that students who learned using the probing prompting model assisted by articulate storyline media obtained significantly higher learning outcomes than students who learned with conventional learning. The average posttest score and the N-gain value of the experimental group were higher than those of the control group, and the results of the independent sample t-test showed a significant difference (p <0.05). These findings indicate that the application of the probing prompting model supported by interactive media is effective in improving student learning outcomes.